Pengaruh Sikap Keuangan Dan Literasi Keuangan Terhadap Pengelolaan Keuangan Pribadi Pada Karyawan PT. Mikuni Indonesia - Siska Dwi Novianti; Yayan Hendayana; Ari Sulistyowati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to assess the influence of financial attitude and financial literacy on personal financial management at PT. Mikuni Indonesia. A quantitative research approach was employed, involving a census sampling technique with a total population of 350 respondents. Data were collected through research instruments and analyzed using statistical methods with SPSS software. The findings reveal that: 1) Financial attitude has a positive and significant impact on financial management, 2) Financial literacy has a positive and significant impact on financial management, and 3) Both financial attitude and financial literacy together positively and significantly affect financial management. These results suggest that improving financial attitudes and literacy can enhance personal financial management practices.